Movimiento foliar en Larrea tridentata (Sessé y Moc. ex DC.) Cov. en relación con la sequía y la edad de la hoja - Valverde, Pedro Luis; Arizaga, Santiago; Ezcurra, Exequiel (Instituto de Ecología, A.C., 1993)
The creosote bush (Larrea tridentata) is a common desert perennial shrub with bifoliate, amphistomatic, divaricate leaves. The leaves can vertically close their folioles and vary their profile with respect to direct solar radiation. A greenhouse experiment was done to evaluate (a) the amount of foliole movement present in creosote saplings and (b) the influence of drought and leaf age on their movement. In the greenhouse, foliole aperture varied significantly with the water status of soil, the hour of the day and the age of the leaf. Folioles opened in the early morning and closed in the late afternoon. Stressed plants showed foliole apertures significantly lower than those of non-stressed plants. Folioles from young leaves were significantly more closed than those from mature or old leaves.